Study on Functional Outcome of Elastic Stable Intramedullary Nailing (ESIN) of Diaphyseal Fractures of Paediatric Long Bones - Vashisht, Arun; Sharma, Gaurav Dev (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
Background: Following the introduction of titanium elastic nails (TENs) and the encouraging results of elastic stable intramedullary nailing (ESIN) in diaphyseal fractures of paediatric long bones, not only are patients' parents choosing surgical treatment over conservative, but more and more orthopaedicians are offering ESIN with TENs to avoid the inherent problems of conservative treatment. Objective of this study was to evaluate the functional outcome of ESIN in diaphyseal fractures of paediatric long bones. Methods: 44 patients aged 5-15 years suffering from diaphyseal fractures of femur, tibia, humerus, and forearm bones were treated by ESIN with TENs. Results: The femur took an average of 8.3 weeks to union, the tibia took 7.3 weeks, the forearm bones took 7 weeks, and the humerus took 7.5 weeks.The most common complication was pain at the insertion site.One femur patient had a 1.5 cm lengthening. Joint stiffness was observed in one femur and one forearm patient. There was no delayed/non-union, sagittal/coronal/rotational mal-union, or deep infection in any of the patients.Partial weight bearing (PWB) began on the second or third day and progressed to full weight bearing (FWB) after 6 to 10 weeks. Conclusions: ESIN with TENs appears rational and safe to avoid the inherent issues of conservative treatment, as it is the least invasive and allows for early PWB/FWB, which leads to early personal hygiene/toilet use independence, as well as early social integration/return to school.